2001
DOI: 10.1046/j.1524-475x.2001.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Noninvasive and Quantitative Methodologies for the Assessment of Chronic Ulcers and Scars in Humans

Abstract: Chronic ulcers are a significant and common cause of morbidity and mortality worldwide. They disrupt the epidermis and dermis, resulting in a loss of barrier function. Keloids and hypertrophic scars (benign cutaneous tumors) represent an abnormal healing response. These fibroproliferative disorders are characterized by an overabundance of collagen and accumulation of extracellular matrix due to an imbalance between synthesis and degradation, culminating in excessive scarring. The objectives of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 39 publications
(47 reference statements)
3
55
1
1
Order By: Relevance
“…Other investigators have documented that blood flow is increased in hypertrophic but not atrophic scars. [22][23][24] These results suggest that diabetic dermopathy lesions are, in fact, scars. Patients typically ascribe their dermopathy lesions to prior trauma.…”
Section: Commentmentioning
confidence: 99%
“…Other investigators have documented that blood flow is increased in hypertrophic but not atrophic scars. [22][23][24] These results suggest that diabetic dermopathy lesions are, in fact, scars. Patients typically ascribe their dermopathy lesions to prior trauma.…”
Section: Commentmentioning
confidence: 99%
“…Recently, high-frequency ultrasound (HFUS) using a 20 megahertz (MHz) probe has been used to provide computer-generated images for both dermatologic diagnostics and research to evaluate lymph nodes, 7 chronic injuries, 8,9 skin lesions, and tumors. 7,[10][11][12] However, the use of 20 MHz HFUS to investigate the development of PrIns is relatively new.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The hypoechogenic areas are thought to reflect increasing fluid content associated with inflammation indicating soft tissue edema before visible damage is noted at the skin surface. 8,10,[13][14][15][16][17][18] HFUS was validated as a sensitive method for changes in dermal hydration associated with edema formation by nuclear magnetic resonance imaging. 19 In the acute care setting, HFUS may be used for documentation, detection, and monitoring of soft tissue injury in patients at risk upon hospital or long-term care admission; however, little is known regarding its accuracy or reliability.…”
Section: Introductionmentioning
confidence: 99%
“…10 Timar-Banu et al used LDF technique and found that, the blood flow in pathological scars was greater than that in normal skin. 18 Qingliang Liu et al used LSCI technique and found that the blood flow in the adjacent skin surrounding keloid tissues was greater than that in nonadjacent skin tissues. 15 Blood flow also changes with the progression of pathological scars.…”
Section: Vascular Structure Of Pathological Scarsmentioning
confidence: 99%
“…15 Blood flow also changes with the progression of pathological scars. Ehrlich's study showed that, at [16][17][18] weeks after wound closure, the blood flow in hypertrophic scars was still three times higher than in normal skin and four times greater than in normal scars. …”
Section: Vascular Structure Of Pathological Scarsmentioning
confidence: 99%